Religion, an obstacle to workplace spirituality and employee wellness? - Bester, Alan (Verbum et ecclesia, 2017)
A desperate need for employee wellness is echoed in work-related stories. Workplace spirituality is presented as an integral part of achieving and maintaining employee wellness. However, there is an observed gap of spirituality in employee wellness programmes and in the absence of the workplace spiritual helper in multidisciplinary wellness teams. Using a postfoundational notion of practical theology, I have explored one of the reasons for this gap, namely workplace spirituality's association to religion. When spirituality is viewed through the lens of religion, it is overlooked as a vehicle of help. This is a consequence of the obstacles of the taboo of religious discussion, the complexity of religious plurality, the dominant voice of secularism and unhelpful religiosity. A proposal is made for a definition of spirituality that describes the relationship between spirituality and religion that overcomes the religionrelated obstacles to the development of workplace spirituality and so enable spirituality's contribution in wellness.Intradisciplinary and/or interdisciplinary implications: The research includes an interdisciplinary collaboration with a Human Resource (HR) manager, social worker, arts therapist, clinical pastoral counsellor, medical practitioner, psychologist, businessperson and two psychiatrists that underscores the collaborative effort in wellness. There is an intradisciplinary challenge to those who restrict the view of spirituality to the experience of religion.